Investigating the perception dimensions of sports disciplines stigma in China: social identity and participation willingness - Wang, Mengkai; Zhang, Yongtao; Wang, Mingtao; Zhao, Xi (Frontiers in Psychology, 2025)
IntroductionThis study aims to explore the dimensions of stigma perception in sports disciplines, focusing on the impact these dimensions have on the public’s willingness to participate in stigmatized sports. The research seeks to identify and analyze the dimensions of stigma, test hypotheses regarding their influence, and investigate the mediating role of social identity in this relationship.MethodsThe study was conducted in China using in-depth interviews with 36 sports enthusiasts, followed by a comprehensive questionnaire survey. Grounded theory was employed for the qualitative analysis of interview data, resulting in the identification of three primary dimensions of stigma: participant group stigma, negative events stigma, and discipline value stigma. Structural Equation Modeling (SEM) and path analysis were utilized to validate the proposed model and analyze the mediating effects.ResultsWe find that all three dimensions significantly influence the willingness to participate in sports disciplines, with negative events stigma having the most substantial impact. Social identity partially mediates the effects of these stigma dimensions on participation willingness, indicating that the perceived stigmas negatively impact social identity and participation willingness.DiscussionThe results underscore the importance of addressing stigma in promoting sports participation. The findings align with existing literature on the negative impacts of stigmatization but extend the understanding by highlighting the mediating role of social identity. The study suggests that efforts to reduce stigma and enhance social identity could significantly boost public engagement in sports. Future research should explore additional mediating variables and the long-term effects of stigma reduction interventions.